2016
DOI: 10.1074/jbc.m115.700484
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Mycobacterium tuberculosis H37Rv AldR (Rv2779c), a Regulator of the ald Gene

Abstract: Feast/famine regulatory proteins (FFRPs), 5 also known as Lrp/AsnC family proteins, bind to a variety of effectors like amino acids that modulate the respective regulatory functions. They are involved in the formation of globular nucleoprotein structures, chromosome structure organization, and other regulatory functions (1). Directly or indirectly, they globally regulate a variety of metabolic processes in response to amino acids and nitrogen bases present in the environment. The general understanding is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…E). This observation suggests an important regulatory function of the “feast and famine”‐type AsnC transcriptional regulator (Kumarevel et al, ; Deng et al, ; Dey et al, ) for the expression of the 5‐hydroxyectoine/ectoine uptake and catabolic gene cluster of R. pomeroyi .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…E). This observation suggests an important regulatory function of the “feast and famine”‐type AsnC transcriptional regulator (Kumarevel et al, ; Deng et al, ; Dey et al, ) for the expression of the 5‐hydroxyectoine/ectoine uptake and catabolic gene cluster of R. pomeroyi .…”
Section: Resultsmentioning
confidence: 98%
“…A) encodes a regulatory protein belonging to the “feast and famine” family of transcriptional regulators (Deng et al, ). These types of regulatory proteins often form octamers wrapping the target DNA around them and their DNA‐binding properties are dictated by small molecules, mostly amino acids (e.g., l ‐Leucine, l ‐Glutamine, l ‐Alanine, l ‐Tyrosine, l ‐Tryptophane, or l ‐Aspartate) (Kumarevel et al, ; Dey et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AsnC exerts a clear activating influence on the expression of the R. pomeroyi hydroxyectoine/ectoine-importer and catabolic gene cluster. AsnC/Lrp-type proteins wrap DNA into nucleosome-like structures and frequently respond in their DNA-binding properties to low-molecularmass effector molecules that are generated through metabolism (e.g., amino acids) (Shrivastava and Ramachandran, 2007;Kumarevel et al, 2008;Dey et al, 2016). In many cases, these proteins respond to feast-and-famine situations and thereby permit the efficient exploitation of sudden burst in the supply of a particular nutrient in fluctuating environmental settings (Yokoyama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…S3). These types of proteins can form octamers wrapping their target DNA around them into a high-ordered tertiary nucleosome-like complex, and their DNA-binding properties are dictated through interactions with low-molecular-mass effector molecules, often amino acids (Yokoyama et al, 2006;Shrivastava and Ramachandran, 2007;Kumarevel et al, 2008;Kamensek et al, 2015;Dey et al, 2016). We have previously demonstrated that the deletion of the last two genes (ssd-atf) in the hydroxyectoine/ectoine catabolic operon (Fig.…”
Section: Influence Of Hydroxyectoine and Ectoine Importer And Catabolmentioning
confidence: 99%